PENGARUH STRUKTUR KEPEMILIKAN DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA - Nuryaman; Rusmin & Joy Nanta Ginting (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2010)
The objectives of the research are to find out empirical evidence of the effect corporate governance mechanisms on earnings management. The corporate governance mechanisms of this research aremanagerial ownership, institusional ownership, and audit quality which measure by industry specialize audit firm. The target population was listed companies in the manufacturing sector at the Indonesia Stock Exchange. The sample determined based on purposive samping methode. There were 80 companies meeting the criteria. Data analysis was carried out in term cross section covering financial report during 2008. The research hyphotesis were tested using multiple regression analysis. The result of this research show that: (1)managerial ownership had significantly negative influence on earnings management (2) institusional ownership had significantly negative influence on earnings management. (3) industry specialize audit firm had no influence on earnings management.